Monitoring Elementary School Students Achievement using Android-based RESTful Web Service - Ilham Yuslin Anugrah; R. Reza El Akbar; Alam Rahmatulloh (Sistemasi: Jurnal Sistem Informasi, 2022)
There are still many elementary schools that have not implemented an information system for processing student grades online. It is because of the assumption that it is still not needed, even though the use of computerized information systems can help schools in improving the academic process to be more effective and efficient. Currently, information systems with web-based applications still have shortcomings. The mobility of their use is still lacking when it is compared to Android-based applications (easier to use and access anywhere). The use of web applications as a means for teachers to input values as well as an android application as a means for parents to be able to monitor their children's academic scores is considered to be the most appropriate solution in implementing this information system, but the differences in platforms between Android and the web make it difficult for data to be integrated each other. Therefore we need an interoperability system to integrate applications from different platforms. Then an android based academic score monitoring application was made with a RESTful web service. The selection of the RESTful web service system itself is because this system applies the concept of a client-server where the server to be created is a web-based application that is used by the school to input student grades, and the client application is an android application intended for parents/guardians of students to get information regarding the value of his child. The output of this research is an application system for monitoring the academic scores of elementary school students by implementing the RESTful web service system in its application as well as the results of the application testing questionnaire based on the usability aspect of the application with the final result of the application eligibility percentage of 87%.